Analysis of immune infiltration in basal cell carcinoma based on transcriptome sequencing and experimental validation of diagnostic biomarkers - Pengfei Fan; Yun Liu; Tengxiao Ma; Qiaoxing Wang; Lei Li (Discover Oncology)
Abstract Background Basal cell carcinoma (BCC) is the most common type of malignant skin tumour, and its incidence is increasing worldwide. While it grows slowly, BCC is locally invasive, causing significant tissue damage. This study investigated the role of mRNAs in BCC through bioinformatics and experimental validation to elucidate the molecular mechanisms involved. Methods Differentially expressed genes (DEGs) were identified from the transcriptome data of 30 BCC patients and 16 controls from the GSE7553, GSE103439, and GSE42109 datasets. Gene Ontology and KEGG analyses were performed to explore gene expression and pathways. A protein‒protein interaction (PPI) network was constructed to identify hub genes, and immune cell infiltration was analysed to study the tumour microenvironment. The diagnostic potential of target genes (LEF1, LGR5, and SOX4) was assessed using ROC curves. Gene expression was validated with qPCR and Western blotting. Results A total of 135 DEGs were identified, with 9 hub genes selected. LEF1, LGR5, and SOX4 showed strong diagnostic potential, with AUC values of 0.888, 0.955, and 0.996, respectively. The immune cell analysis revealed increased numbers of B cells, NK cells, and T cells in BCC, whereas the numbers of DCs, pDCs, and Treg cells were reduced. qPCR and Western blotting confirmed increased LEF1 and LGR5 expression in BCC. SOX4 expression was increased according to the qPCR results but was not significantly elevated according to the Western blot results, warranting further validation. Conclusions LEF1, LGR5, and SOX4 may play roles in BCC pathogenesis and could serve as diagnostic biomarkers. These findings provide insights into BCC development and support future research for improved detection and treatment.